Risk factors of mortality in hospitalized children with severe acute malnutrition - Bidhan Chandra Podder; Minara Sikder; Rubina Bari; Dipannita Dhar; Anjumanara Begum; Farjana Sarmin; Ahmed Nazmul Anam; Sarmin Sultana Swarna (International Journal of Research in Medical Sciences, 2023)
Background: Severe acute malnutrition (SAM) is a major cause of morbidity and mortality in children around the world. It is critical to identify the factors that contribute to mortality to reduce SAM related mortality. This study aimed to analyze the risk factors of mortality in hospitalized children with SAM. Methods: This case-control study was conducted in the SAM unit, department of pediatrics, institute of child and mother health, Matuail-1362, Dhaka, from January 2021 to December 2021. Data analysis was conducted using SPSS version 22. Univariate analysis was done to determine factors affecting mortality, and multivariate logistic regression was used to determine significant independent risk factors. Results: Mean age of the study subject was 6.38±3.45 months and 10.90±10.00 months in the case and control groups respectively. So, death was more common in younger children. The percentage of death was more (61.5% vs 54.6%) in males. Mortality was more common in family income <10,000 Tk/ month, 53.8% in the case group and 21.9% in the control group. The mean age of the mother was 19.23±0.60 years and 21.78±4.78 years in the death and survived group. Among risk factors of mortality, dermatosis (46.2% vs 4.9%), oral ulcer (46.2% vs 5.5%), hypoglycemia (46.2% vs 3.8%), severe anemia (38.5% vs 2.2%), septicemia (76.9% vs 29.5%) in case and control group respectively. These risk factors were significantly higher in the death group compared to the surviving group. After doing multivariate logistic regression analysis it was observed that hypoglycemia (OR=9.17 with 95% CI 1.44 to 58.29) and severe anemia (OR=13.42 with 95% CI 1.42 to 126.13) were the strongest predictors of mortality among the hospitalized children with SAM. Conclusions: Hypoglycemia and severe anemia were the main contributing factors of mortal among the children with SAM in the hospital.